al- Ḥallāǧ al-aʿmāl al-kāmila ; at-Tafsīr, aṭ-Ṭawāsīn, Bustān al-maʿrifa, Nuṣūṣ al-wilāya, al-Marwīyāt, ad-Dīwān - Ḥallāǧ, al-Ḥusain Ibn-Manṣūr al- 858-922 (Riyāḍ ar-Rayyis lil-Kutub wa-'n-Našr, 2002)
Sufism; author's complete works